Privacy as a Matter of Public Health - Lev-Aretz, Yafit; Nielsen, Aileen (Science and Technology Law Review, 2025)
This Article examines the striking parallels between contemporary privacy challenges and past public health crises involving tobacco, processed foods, and opioids. Despite surging state and federal privacy legislation, many of these new privacy law and policy activities follow familiar patterns: an emphasis on individual choice, narrowly defined rights and remedies, and a lack of holistic accounting of how privacy incursions affect society as a whole. We argue instead for a salutary shift in privacy law and advocacy: understanding privacy through the lens of public health. By tracing systemic factors that allowed industries to repeatedly subvert public welfare—from information asymmetries and regulatory capture to narratives of individual responsibility—we explore a fundamental rethinking of privacy protection. Our analysis of case studies reveals remarkable similarities between public health challenges of the past half-century or so and the ongoing consumer privacy crisis. We explore how public health frameworks emphasizing preventative policies and reshaping social norms around individual choices could inform privacy advocacy. To do so, we examine a spectrum of proposals to align privacy with public health, from adopting public health insights to provocatively reframing privacy violations as an epidemic threatening basic wellbeing. This Article offers a novel framework for addressing the current privacy crisis, drawing on the rich history and strategies of public health. In reframing privacy violations as a societal health issue rather than a matter of consumer choice, we see new avenues for effective regulation and protection. Our proposed approach not only aligns with successful public health interventions of the past but also provides a more holistic and proactive stance towards safeguarding privacy in the digital age.